A synthesis for managing invasions and pest risks simultaneously for tephritid fruit flies in South Africa. Issue 5 (14th March 2018) - Karsten, Minette; Barton, Madeleine; Addison, Pia; Addison, Matthew F.; Terblanche, John S.
Abstract: Developing a general management framework for monitoring and reporting biological invasions in agricultural contexts is crucial to assist in the planning and execution of intervention and control strategies. Here we make use of a diverse range of data sets for economically significant South African agricultural fruit fly pests to offer several potential intervention strategies and present a general management framework that unifies different but related fields of research (invasion science and pest management). We review the status of Tephritidae (Diptera) in South Africa with a strong focus on the highly invasive Bactrocera dorsalis (Hendel) and touch on the use of population genetics in pest or invasion management. Integrated modelling of landscape friction from population genetics is undertaken to test for any intrinsic resistance to pest movement across the landscape (e.g., natural or agricultural barriers). Based on the novel analyses presented here, clearly defined landscape management units can be allocated. Across South Africa, control and intervention strategies for managing both invasions of new Tephritidae and existing pest species can be unified into a common framework. Finally, we illustrate the concepts outlined above in a conceptual management decision tree for integrating pest management and invasion management simultaneously. Promoting awareness among growers and the public about fruit fly invasions and impacts is a priority to prevent future incursions of fruit flies, whereas managing Tephritidae as distinct landscape units should facilitate prevention of movement of emerging and existing pests. Abstract : The Tephritidae (Diptera) are pests of economic significance in South Africa, most notably the recent invader Bactrocera dorsalis . Here, we propose a general management framework for the monitoring and reporting of biological invasions in agricultural contexts. We also illustrate the use of landscape friction models to prioritize management units. These distinct landscape units can aid in the prevention of new invasions as well as the spread of existing pests.